Commune reiventing hostel culture for an inclusive Liwliwa coastal community - Casal, Juliann Christiana C.; Ong, Simoun (Quezon City College of Architecture, University of the Philippines Diliman, 2018)
The Commune is a project that aims to address the lack of inclusivity of the locals with their own beach. It is proposed to be a free hostel that adopts a work-for-free-accommodation concept, wherein guests have to work for a specified amount of time to compensate for their stay in the hostel. With sustainability and efficiency of design as core ideals in the design process, the project adopted principles of biophilic design. With biophilic design strategies and the integration of Liwliwa's context and culture as the forefront basis for design, isolation, imposition, and exclusivity from the rest of the coastal community will be eliminated and prevented. The project then utilized natural materials indigenous to San Felipie. Bambusa blumeana (tinik) and schizostachyum lumampao (buho) bamboo were used as the main construction materials of the structure, and as bamboo possess both great aesthetic and mechanical qualities, the bamboo's structural design was developed to the the architectural translation of the design approach and agenda. The structural design then continues to innovate on natural and recycled materials by adoopting Architect Simon Velez's bamboo join method using bamboo and used glass or plastic bottles. The system is also constructed in a modular manner, allowing for easy expansion and efficiency in construction.
Include appendices
Thesis (Bachelor of Science in Architecture)--University of the Philippines Diliman
Keywords: Hotels; Tourist camps, hostels, etc; Tourist camps, hostels, etc. -- San Felipe -- Zambales